Supporting and sustaining centralized reminder/recall for immunizations: Qualitative insights from stakeholders. Issue 44 (16th October 2019) - Fisher, Michael P.; Gurfinkel, Dennis; Szilagyi, Peter G.; Saville, Alison; Albertin, Christina; Breck, Abigail; Valderrama, Rebecca; Kempe, Allison
Abstract: Centralized reminder/recall (C-R/R) is an evidence-based strategy for increasing vaccination rates that uses a population-level database such as a state immunization information system (IIS) to send notifications across large geographic areas. IISs are usually based in state public health departments, which could initiate C-R/R. While C-R/R is a promising strategy, the factors influencing its initiation and sustainment are not clear. Utilizing qualitative content analysis methodology and interviews with key stakeholders involved in or knowledgeable about C-R/R, we examined the characteristics of these initiatives and factors influencing their success. We identified and spoke with managers and senior leaders across IISs, health plans, health systems, pharmaceutical companies, and advocacy organizations and focused especially on C-R/R activities within IISs. Several considerations were determined important to C-R/R success: decision-making, stakeholder buy-in, partnerships, funding, data and technology, evaluation, and message content. Salient barriers were costs and lack of funding, poor contact data quality (i.e. telephone number, home address), and messaging that is either overly broad or too specific. Pertinent facilitators of C-R/R included notifying health providers in advance of an initiative, conducting a rigorous post-reminder/recall evaluation, and engaging a range of partners. Partnerships were important to stakeholders for multiple reasons including technical assistance, resource sharing, and sharing of best practices. Overall, our results illustrate the many opportunities to advance C-R/R through further collaboration within and across public health departments and potentially via public-private partnerships.